A compromise view of the tariff - White, Thomas F. (My University, 1906)
Introduction: Before treating this subject it is desirable to set forth clearly the distinction between tariff, protection, and free trade. Tariff is a schedule of duties or imposts levied on goods as they pass from one state to another. A tariff may be levied upon foreign goods simply for enlarging the revenues of a government, in which case it may be termed taxation; as a means of retaliating upon foreign governments for similar restrictions imposed by them, it becomes an instrument of war fare, designed to secure commercial reciprocity. A protective tariff is a means of fostering particular industries by protecting them wholly or in part against foreign competition encouraging and developing home industries by means of either bounties paid to home producers or of duties imposed upon goods imported from abroad. Free trade at present is designated as either entirely unrestricted or restricted only in ways that afford no protection to home industries. Free Trade as first designated by the English was trade open to all merchants, as distinguished from that which was monopolized by chartered trading companies. Unrestricted free trade exists only in the imagination of economists as no government has tempted to put it into practice. Restricted free trade is actually realized in the policy of the United Kingdom. The security of liberty, happiness, and prosperity is the right of every American citizen, and the security of this liberty. Happiness and prosperity depends greatly on the manner in which our laws governing trade are adjusted. At the present time our Country is in a favorable condition but there is no reason why the well fare of the people should not be enhanced. The question of a tariff in this country has been a lively one ever since the foundation of the Republic, and is likely to remain an issue with us for years.
Citation: White, Thomas F. A compromise view of the tariff. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Economics; Tariffs; Free Trade; Proctection; Theses